Cabaré das Divinas Tetas: intersections between clown, drag art and feminisms (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article is about the context where the platform Divinas Tetas of Belo Horizonte was raised, a brief analysis of the way of articulation of women clowns in the capital of Minas Gerais on the first two decades of the 21st century, and the questions about the concepts of female clowns, drag art, gender and feminisms. It is a case study in the “clowning” and “cabaristic” paths that constitute part of the trajectory of the female clown movement in Belo Horizonte. Or (to be more direct clowns) who are the Divinas Tetas, where they live, what they eat, how they reproduce. This article brings as theoretical and bibliographical references the authors Lili Castro, Daiani Brum, Ana Fuchs, Melissa Caminha, Erminia Silva, Renata Saavedra, Cleber Braga, Judith Butler, Manuela Castelo Branco de Oliveira and Neyde Veneziano.
Keywords: Clowns; Circus; Drag art; Feminist art; Cabaret